STUDI HISTORIS PERKEMBANGAN TAREKAT QODIRIYAH DAN PENGARUH DAKWAHNYA DI INDONESIA - Laila, Izzatul (Dinamika, 2013)
ABTRACTRousseau invited researcher about 257 years in the past, to back to the nature.  It will purify the image of human beings trough spiritual activities.  In this case, human beings will fell the attendance of God in the universe and daily life.  This view is developed by Qodiriyah Tarekat Followers.Kata Kunci: Studi Perkembangan, Tarekat Qodiriyah, Pengaruh Dakwah.